Проблема информатизации образования в школе - Sablia T. E. (Upbringing and education: theory, methods and practice, 2017)
Abstract: the article considers new approaches to education in the natural Sciences, a combination with humanitarian disciplines and techniques of educational work.
Keywords: информационные технологии; образование; школа; учащиеся; интеллект; Information technology; intelligence; ability; требования к специалисту; требования к руководителю; Key words: natural science education